Biosynthesis and Characterization of Biogenic Tellurium Nanoparticles by Using Penicillium chrysogenum PTCC 5031: A Novel Approach in Gold Biotechnology - Barabadi, Hamed (Iran J Pharm Res, 2018)
Production of nanoparticles has been attractive by biological based fabrication as an alternative to physical and chemical approaches due to exceeding need to develop safe, reliable, clean and eco-friendly methods for the preparation of nanoparticle for pharmaceutical and biomedical applications. In the present study, biogenic tellurium nanoparticles (TeNPs) were successfully prepared using potassium tellurite (K(2)TeO(3), 3H(2)O) via an eco-friendly and simple green approach by exploiting extracellular enzymes and biomolecules secreted from Penicillium chrysogenum PTCC 5031 at room temperature for the first time. The biofabricated TeNPs were characterized by Atomic Force Microscope (AFM), Scanning Electron Microscopy (SEM), Dynamic Light Scattering (DLS), Energy Dispersive X-ray spectroscopy (EDX), and Fourier Transform Infrared (FT-IR) spectrum. The AFM and SEM images revealed that the TeNPs were fairly uniform in size with a spherical shape and superior monodispersity. Furthermore, the DLS indicated that the average hydrodynamic diameter of TeNPs was around 50.16 nm and polydispersity index (PdI) of 0.012. The EDX results depicted that TeNPs display an absorption peak at 3.8 keV, indicating the presence of the elemental tellurium. Additionally, the FT-IR analysis of TeNPs exhibited the presence of possible functional groups that may have a role as bioreducers and capping agents. Overall, the results strongly suggested that P. chrysogenum can be a potential nanofactory for the preparation of TeNPs due to several advantages including non-pathogenic organism, fast growth rate, and high capacity of elemental ions reduction, as well as facile and economical biomass handling.